2012
DOI: 10.1007/s10959-012-0409-4
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Eigenvalue Distributions of Block-Transposed Wishart Matrices

Abstract: Abstract. We study the partial transposition W Γ = (id ⊗ t)W ∈ M dn (C) of a Wishart matrix W ∈ M dn (C) of parameters (dn, dm). Our main result is that, with d → ∞, the law of mW Γ is a free difference of free Poisson laws of parameters m(n ± 1)/2. Motivated by questions in quantum information theory, we also derive necessary and sufficient conditions for these measures to be supported on the positive half line. IntroductionThe partial transposition of aΓ obtained by transposing each of the n × n blocks of W … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 7 publications
7
63
0
Order By: Relevance
“…He computed the range of parameters of the Wishart distribution for which the partial transposition is still positive. Similar computations, in different asymptotic regimes, or for different maps acting on the blocks, have been performed in [BN12a,FŚ13,JLN14,JLN15]. In this paper, we unify these results by showing that operatorvalued free probability theory provides the right framework to study such questions.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…He computed the range of parameters of the Wishart distribution for which the partial transposition is still positive. Similar computations, in different asymptotic regimes, or for different maps acting on the blocks, have been performed in [BN12a,FŚ13,JLN14,JLN15]. In this paper, we unify these results by showing that operatorvalued free probability theory provides the right framework to study such questions.…”
supporting
confidence: 57%
“…In the case where the measure µ is a free Poisson measure of parameter λ > 0, we recover Theorem 4.1 from [BN12a]:…”
Section: Distribution Of the Productmentioning
confidence: 73%
See 1 more Smart Citation
“…The PPT criterion for random quantum states has first been studied numerically in [ŽPBC07]. The analytic results in the following proposition are from [Aub12] (in the balanced case) and from [BN13] (in the unbalanced case); see also [FŚ13] for some improvements in the balanced case and the relation to meanders.…”
Section: 3mentioning
confidence: 99%
“…This case has been studied in [8,Theorem 6.2], where it has been shown that the measure MP Γ has positive support iff…”
Section: Propositionmentioning
confidence: 99%